Hydrogels design, synthesis and application in drug delivery and regenerative medicine - Singh, Thakur Raghu Raj; Laverty, Garry; Donnelly, Ryan (Taylor & Francis, 2021)
Hydrogels are crosslinked, macromolecular polymeric materials arranged in a three-dimensional network, which can absorb and retain large amounts of water. Hydrogels are commonly used in clinical practice and experimental medicine for a wide range of applications, including drug delivery, tissue engineering and regenerative medicine, diagnostics, cellular immobilization, separation of biomolecules or cells, and barrier materials to regulate biological adhesions. This book elucidates the underlying concepts and emerging applications of hydrogels and will provide key case studies and critical analysis of the existing research